भारतीय संस्कृति में वर्तमान पर्यावरणीय समस्याओं का स्थायी समाधान - Manoj Kumar Rao (Dr. Chinmay Pandya, 2013)
इक्कीसवीं सदी विज्ञान एवं तकनीकी का युग है। इस विज्ञान एवं तकनीकी के माध्यम से वर्तमान युग में भौतिक समृद्धि एवं साधनों की अपार वृद्धि हुई है। प्राकृतिक संसाधनों के माध्यम से व्यापक स्तर पर भौतिक जीवन के साधनों का निर्माण हो रहा है। प्राकृतिक संसाधनों के असीमित दोहन के कारण जहाँँ एक तरफ पारिस्थितिकीय असंतुलन उत्पन्न हो रहा है वहीं दूसरी तरफ उद्योगों एवं विविध प्रकार के मानव निर्मित भौतिक साधनों से उत्सर्जित हानिकारक तत्वों से पर्यावरण प्रदूषण बड़ी तेजी से बढ़ रहा है, जिसके फलस्वरूप आए दिन लोगों को सर्वनाशी समस्याओं का सामना करना पड़ रहा है। आज जहाँ जीवन को सुखमय और खुशहाल बनाने की चाह है वहीं अपने अस्तित्व को खो देने का भय भी है। मानवीय अस्तित्व की रक्षा के लिए इन समस्याओं का समाधान अति आवश्यक है। इन समस्याओं का स्थायी समाधान एक मात्र भारतीय संस्कृति की प्रकृति विषयक आध्यात्मिक चिंतन में है जिसको अपना कर मनुष्य अपने सुख, समृद्धि एवं अस्तित्व के साथ-साथ पर्यावरण को भी सुरक्षित तथा संरक्षित रख सकता है। प्रस्तुत शोध पत्र में भारतीय संस्कृति की उन्हीं प्रकृति रक्षक श्रेष्ठ एवं आदर्श सूत्रों को उजागर किया गया है। Twenty-first century is the era of science and technology. The material affluence and resources have escalated tremendously in the present age with the advancements in science and technology. The means of materialistic life are being established on a wide scale through natural resources. Where the extensive exploitation of natural resources has caused ecological imbalance on one hand, harmful elements emitted from industries and various man-made substantial means have induced environmental pollution on the other hand causing people to experience catastrophic problems. Today, where there is a longing to flourish life, delightful and prosperously, also undergoes the fear of losing our existence. The solution for these problems is indispensable to preserve human existence. The imperishable solution to these problems lies in the spiritual contemplation of the essence of Indian culture, through whose integration a person can protect and preserve his happiness, prosperity and existence along with the conservation of the environment. In the presented paper, the nature's safeguards and ideal sources of Indian culture have been scrutinized.